PERENCANAAN LAMPU LALU LINTAS (TRAFIC LIGHT) PADA SIMPANG EMPAT JALAN RAJAWALI – JALAN BADAK PALANGKA RAYA (Planning Of Traffic Lights (Trafic Light) On Four Junctions Of Rajawali Road - Jalan Badak Cross Circle) - Aria Hansen (Fakultas Teknik Universitas Kristen Palangka Raya, 2021)
Palangka Raya is a city that is developing and has the potential for population density, besides that it has the potential in the fields of education and government so that it attracts people from outside the region to come to the city. This will have an impact on traffic flow, especially on roads that have intersections. Especially at the intersection on the road Rajawali - Badak, a traffic light plan was held to be used as a final project research. Installation of traffic lights on intersection roads serves to facilitate orderly and safe traffic movement so as to increase road capacity at intersections, reduce the frequency of various types of accidents and cut off high traffic flows to allow for the spread of vehicles or pedestrians. To plan the traffic lights we use calculations with the Webster method. The calculations performed only determine the cycle time. The results obtained from the traffic light planning at the intersection of the Rajawali - Badak road are that the cycle times are obtained faster so that the queue of vehicles that stop at the intersection is not too long and does not cause congestion. Keywords: Traffic Lights, Webster Method, Cycle Time, Queues and Congestion.